Correlates of Knowledge and Adoption Behaviour of Farmers with their Profile Characteristics : An Analysis of Chrysanthemum Growers in Mandya District of Karnataka - Mamathalakshmi, N. K. Nagabhushanam, M. S. Nataraju, H. S. Surendra , B. Krishnamurthy, Sowmyashree G.T. (Indian Journal of Extension Education, 2022)
..